Specific Features of Neonatal Artificial Ventilation in Different Stages of Correction of Visceroabdominal Disproportion - D. V. Dmitriyev; K. T. Bertsun; A. A. Nazarchuk; A. V. Katilov (Общая реаниматология)
Objective: to optimize artificial ventilation on the basis of studies of lung mechanical properties in neonatal infants with visceroabdominal disproportion in the perioperative period. Subjects and methods. The investigation enrolled 57 neonates, including 42 (73.7%) with gastroschisis and 15 (26.3%) with omphalocele. All the patients received intensive care, artificial ventilation using a Bear Cub apparatus in the control modes by the volume (A/C, SIMV/PSV) with continuous monitoring of hemodynamics and respiratory mechanics (dynamic compliance, resistance, pressure-volume loop, and flow-volume) by applying a graphics monitor. Intraabdominal pressure (IAP) was measured by the Crohn method. Results. The investigation showed an association between the changes in IAP in different stages of the study and those in respiratory parameters in newborns. Preoperative adaptation of the respiratory system was noted in all the neonates. Within the first 24 hours of the first-stage correction of visceroabdominal disproportion, both groups showed a gradual reduction in dynamic compliance by 3.4 times, a rise in resistance by 2.42 times with PIP being increased up to high figures — 20—22 cm H2O, as well as maximum value changes on the graphics monitor. The mechanical properties of the lung returned to relatively normal values at 72 hours of extension. Conclusion. Elevation of IAP to high values causes changes in respiratory mechanics and is a rather informative criterion for correction of ventilation parameters. Furthermore, a marked perioperative IAP increase (more than 10—11 mm Hg) maximally affects the mechanical properties of the lung in neonatal infants with visceroab-dominal disproportion. Key words: visceroabdominal disproportion, intraabdominal pressure, compliance, respiratory mechanics, resistance.